2015
DOI: 10.1038/ncomms7382
|View full text |Cite
|
Sign up to set email alerts
|

A mechanically sensitive cell layer regulates the physical properties of the Arabidopsis seed coat

Abstract: Endogenous mechanical stresses regulate plant growth and development. Tensile stress in epidermal cells affects microtubule reorientation and anisotropic cell wall deposition, and mechanical stimulus at the meristem regulates trafficking and polar localization of auxin transporters. However, the mechanical regulation of other plant growth regulators has not been demonstrated. Here we propose that during seed growth, mechanical stress exerted by the expanding embryo and endosperm is perceived by a specific mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 33 publications
12
73
0
Order By: Relevance
“…4A). In a previous study, we showed that soon after fertilisation, endosperm-derived pressure is perceived in an internal cell layer of the seed coat (the inner cell layer of the outer integument), which subsequently undergoes thickening of its inner cell wall (Creff et al, 2015). We considered this cell wall to be load-bearing, and other cell walls to have small contributions to seed mechanics before the completion of cellularisation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A). In a previous study, we showed that soon after fertilisation, endosperm-derived pressure is perceived in an internal cell layer of the seed coat (the inner cell layer of the outer integument), which subsequently undergoes thickening of its inner cell wall (Creff et al, 2015). We considered this cell wall to be load-bearing, and other cell walls to have small contributions to seed mechanics before the completion of cellularisation.…”
Section: Resultsmentioning
confidence: 99%
“…Seed development involves the coordinated growth of maternal seed coat tissues and the enclosed zygotic endosperm and embryo. In Arabidopsis, rapid expansion of the coenocytic endosperm after fertilisation has been proposed to drive early seed growth, which is in turn constrained by the seed coat (Creff et al, 2015;Garcia et al, 2005Garcia et al, , 2003Ingram, 2010). The growing seed is a major sucrose sink, and sucrose import from the testa to the endosperm plays an important role in Arabidopsis seed development (Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Embryo growth is dramatically reduced in zou mutants, owing to an apparent inability of the embryo to expand into the persistent endosperm (Yang et al, 2008). The idea that the embryo is physically constrained in this background is supported by the fact that the testa in zou mutants is under greater tension than that in wild-type plants after endosperm cellularisation (Creff et al, 2015), suggesting that the expanding embryo and the abnormally persistent endosperm compete for space within the seed cavity.…”
Section: Introductionmentioning
confidence: 61%
“…In Arabidopsis, growth of the expanding coenocytic endosperm during early post-fertilisation development drives seed expansion, which is in turn controlled by the seed coat in order to achieve a genetically determined final seed size and shape (Garcia et al, 2005(Garcia et al, , 2003Ingram, 2010). More recently, it has been shown that seed coat expansion is regulated by a specific cell layer, the adaxial epidermis of the outer integument, at least in part in response to mechanical tension imposed by the growing endosperm (Creff et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that, in this more complex system, mechanical tension accumulates not in the outermost seed coat epidermal cell layer, but in the cell layer beneath it (the adaxial epidermis of the outer integument). The outer cell wall of this epidermal cell layer, which in reality is buried within the developing seed coat, is the thickest periclinal wall in the seed coat and appears to be loadbearing (Creff et al, 2015). In both these examples, patterns of cortical microtubule reorientation were used as directional reporters for tissue tension; changes in tensile stress patterns in the epidermis are known to affect cortical microtubule orientation, which can in turn be used as a readout of tensile stress direction (Hamant et al, 2008;Sampathkumar et al, 2014).…”
Section: Box 1 Glossarymentioning
confidence: 99%